Trophic Enrichment Factors of Carbon and Nitrogen Isotopic Ratios (Δ13C and Δ15N) in Four Marine Ciliates - Park, Jun Young; Jung, Jae-Ho; Kwak, Jung Hyun; Park, Heum Gi; Kang, Chang-Keun; Park, Hyun Je (Frontiers in Microbiology, 2021)
Understanding the magnitude and causes of isotopic fractionation between organisms and their dietary resources is crucial for gaining knowledge on stable isotope ecology. However, little is known regarding the diet-tissue fractionation values of marine ciliates, which play a critical role in the reconstruction of microbial food webs. In the present study, we conducted experiments on two benthic (Pseudokeronopsis pararubra and Protocruzia labiata) and two pelagic (Strombidium sulcatum and Uronemella filificum) marine ciliates, where they were fed with isotopically constant foods (Chaetoceros calcitrans and Isochrysis galbana) under laboratory culture conditions to determine their carbon and nitrogen isotopic fractionation values (Δ13C and Δ15N). The stable isotope values (δ13C and δ15N) of ciliates for all experiments rapidly increased after the initial feeding, with half-lives ranging from 6.1 to 23.0 h for δ13C and from 3.1 to 24.9 h for δ15N. The Δ13C and Δ15N for all ciliates represented significantly positive enrichments, with overall mean fractionations of 0.6 ± 0.2 and 1.2 ± 0.4, respectively. Irrespective of the dietary type, both Δ13C and Δ15N were very similar for the same ciliate species. These results suggest that Δ13C and Δ15N for marine ciliates are similar to those found in common marine organisms with very little food-dependent variation. Overall, quantifying the specific isotopic fractionation of marine ciliates is expected to provide fundamental information on the trophic transfer of carbon, nitrogen, and energy flow through the microbial pathway in marine ecosystems.